Designing Task-Based Language Teaching to Foster Confidence, Collaboration, and Performance: Teachers' Perspectives from Indonesian EFL Classrooms - Mia Artin Nur Latifah; S Suharyanto (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to determine the perspectives of English Language (EFL) teachers at the junior high school level towards TBLT, how teachers design and implement task-based speaking classes, especially regarding how to improve students' confidence, collaboration, and speaking performance, as well as the challenges and methods used to overcome these challenges. Methodology: The researchers employed a qualitative descriptive strategy. Data was collected at Al Abidin Islamic Junior High School in Surakarta through classroom observations, semi-structured interviews with three English teachers, and documentation. The data analysis approach adopted by Miles and Huberman (1994) included data reduction, data presentation, and Results: The findings of this study indicate that teachers have very positive attitudes toward TBLT, are more flexible, motivated, and prefer using the TBLT approach compared to traditional techniques such as PPP and CLT. Teachers stated that they structure assignments according to students' abilities, needs, and learning styles, and use diagnostic tests to differentiate assignments. Group presentations, role-playing, and realistic simulations such as vlogs and situational discussions are also frequently used in its implementation. Differences in student ability levels, limited vocabulary, lack of confidence, and time constraints are obstacles encountered in learning activities. Teachers address these issues with personalized instruction, language support, and the creation of an engaging learning environment through games and other activities.Applications/Originality/Value: This study has the advantage of emphasizing the importance of a teacher in providing appropriate speaking activities to increase confidence, collaboration, and speaking performance in English as a Foreign Language, as well as providing practical solutions to overcome challenges in the classroom. This shows that TBLT is a versatile and effective conceptual framework.